Feasibility Study of the Application of Geothermal Energy as a Complementary Source of the Energy Matrix of the State of Mato Grosso (Research, Society and Development, 2018)
The world needs energy to continue its development. One of the most promising sources is geothermal energy that is stable and does not depend on weather conditions. Brazil has a potential to exploit this energy. The objective of this article is to present a feasibility analysis of the implementation of the energy matrix of the state of Mato Grosso through the implementation of Geothermal plants, avoiding sudden oscillations in the supply. An indirect source documentary research is carried out in which data and information about the potential of the use of this energy in the Central West region of Brazil is carried out. The data point to the possibility of use mainly in the State of Mato Grosso and this energy source may become an important strategic reserve for the country.